Nutritional, medicinal and biological activities of Ferocactus species: Recent findings and research opportunities - Faleye, Bosede Ruth; Flores-Gallegos, Adriana Carolina; Ascacio- Valdes, Juan Alberto; Esparza-Gonzalez, Sandra Cecilia; Silva-Belmares, Sonia Yesenia; Nery-Flores, Sendar Daniel; Campos-Muzquiz, Lizeth Guadalupe; Rodriguez-Herrera, Raul (Plant Science Today, 2025)
Ferocactus is a genus of the family Cactaceae found in the arid and semi-arid regions of the American continent, especially in Mexico. The species serve various purposes such as food, cosmetics, fodder and for relief from certain ailments. The fruits of Ferocactus species such as Ferocactus herrerae and Ferocactus glaucescens have valuable amounts of macronutrients, micronutrients and bioactive components which make them nutrient-dense. They are also a potential raw material for new product development in the food and cosmetic industries, industrial extraction and production of antimicrobials and antioxidants. However, many of the species are understudied, underproduced, underutilized or overexploited, resulting in a significant waste or risk of extinction due to overexploitation. Therefore, the objective of this review was to discuss and provide an in-depth and recent overview of the description, morphology, ethnobotanical uses, nutritional composition, bioactive composition and biological activities of different species of Ferocactus reported in the literature from different databases such as Google Scholar, ResearchGate and Scopus. Proper exploration and maximization of these species of cactus can provide huge economic, technological and nutritional benefits for all. Moreover, the challenges, possible solutions and future directions for maximum production and utilization of these species have also been discussed.